2011
DOI: 10.1371/journal.pone.0021865
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Engineered Nanoparticles on the Assembly of Exopolymeric Substances from Phytoplankton

Abstract: The unique properties of engineered nanoparticles (ENs) that make their industrial applications so attractive simultaneously raise questions regarding their environmental safety. ENs exhibit behaviors different from bulk materials with identical chemical compositions. Though the nanotoxicity of ENs has been studied intensively, their unintended environmental impacts remain largely unknown. Herein we report experimental results of EN interactions with exopolymeric substances (EPS) from three marine phytoplankto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 59 publications
2
73
0
Order By: Relevance
“…In contrast, the concentration of carbohydrates from the TWEEN extract was significantly higher only at the highest concentration of DWCNTs. As already observed with polystyrene nanoparticles [60], our results suggest a strong hydrophobic interaction between DWCNTs and EPS, which is mainly driven by PLPs. These results corroborate the HPLC results, which showed increases in two PLPs ($174 kDa, $10 kDa) that could be strongly implicated in the observed hydrophobic interaction between EPS and DWCNTs.…”
Section: Interactions Between Dwcnts and Epssupporting
confidence: 86%
See 1 more Smart Citation
“…In contrast, the concentration of carbohydrates from the TWEEN extract was significantly higher only at the highest concentration of DWCNTs. As already observed with polystyrene nanoparticles [60], our results suggest a strong hydrophobic interaction between DWCNTs and EPS, which is mainly driven by PLPs. These results corroborate the HPLC results, which showed increases in two PLPs ($174 kDa, $10 kDa) that could be strongly implicated in the observed hydrophobic interaction between EPS and DWCNTs.…”
Section: Interactions Between Dwcnts and Epssupporting
confidence: 86%
“…TWEEN 20 was used as a chemical substitute for hydrophobic bonds [59], freeing the EPS linked by hydrophobic interactions to DWCNTs. Considering the high solubility of polysaccharides, the hydrophobicity of EPS is mostly inherent to proteins [49,60]. In this study, carbohydrates and PLPs from the TWEEN extract were strongly correlated ($0.95) with the concentration of DWCNTs.…”
Section: Interactions Between Dwcnts and Epsmentioning
confidence: 59%
“…In the scientific literature both, uptake of NPs by microbial cells [36] [37] [24] as well as increased dissolution of NPs in the vicinity of microbial cells have been suggested [38] [39] [40]. In case of three marine phytoplankton species exposure to polystyrene NPs increased the production of exopolymers [41] which indicates that NPs may significantly interfere with cellular physiology. However as the interaction of NPs with living cells and vice versa is a dynamic process, determination of the exact sequence of cellular events triggered by NP exposure remains to be elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6F shows gum-like cellulose surrounding the microalgae. Previous studies have shown that the interaction between NPs and phytoplankton produced EPS [19,44]. The increased production of EPS was found to be a general response to the presence of pollutants [45].…”
Section: Resultsmentioning
confidence: 99%